O uso de analogias para o ensino de equilíbrio químico no ensino médio: facilitação da aprendizagem ou transmissão de erros conceituais? - Silva Junior, Olimpio Jose da (2013)
The use of analogies in high school is often useful for chemistry teaching, either on textbooks or by teachers in the classroom.This use is justified by the large number of abstract concepts that rules this course. Analogies are conceptualized by several authors, which converge on the idea that these are tools that seek a way to elucidate an unknown concept by comparing it to a familiar one, relating their similar and dissimilar features. An analysis on a survey of analogies found in high school chemistry textbooks and chemical equilibrium studies is performed in order to verify whether they are leading to misconceptions for their use by students and/or for their use by teachers in the classroom, or whether they promote a learning facilitation